Congestion Aware Multi-Path Routing Protocol with Load Balancing - K.Sangeetha Supriya; M.Gopi Chand; K.Raja Sekhar (International Journal of Advances in Applied Sciences, 2017)
The multi-path routing protocol is one of the approaches used to have less overhead, better bandwidth cost through the load distribution among a set of paths. However, due to the interference of the paths during the communication, it increases the end to end delay and do not work well under a highly congested network. We have proposed the congestion aware multi-path routing protocol with load balancing. The paper explains the problem associated with the end-to-end delay. It deals with the problem of channel interference during the Multi-path communication. It suggests the congestion control mechanisms to improve the protocol performance. It proposes an additive increase/ multiplicative decrease and fast retransmits and recovery process and also it suggest the algorithm for load balancing scheme. In order to minimize the congestion formation, it selects the node disjoint paths for communication. The correlation factor among the selected multiple paths are calculated. It calculates the congestion formation in the network. It compares the proposed MPR protocol with ordinary DSR through the simulation and the simulation results are discussed.